Optimizing the Communication Skills of Islamic Education Teachers to Strengthen Students' Congregational Prayer Habits - Rayani, Siti; Amini, Nur Rahmah; Tanjung, Ellisa Fitri (Universitas Nahdatul Ulama Surabaya, 2024)
This study aims to examine the communication skills of Islamic Religious Education (PAI) teachers in fostering the habit of congregational prayer among students at SD Islam Terpadu Anak Sholeh in Langkat Regency. This study used a qualitative descriptive method by utilizing interviews, observations, and documentation for data collection. The results showed that PAI teachers effectively communicated the significance of congregational prayer through various methods, including short lectures, inspirational stories, and demonstrations, all of which were adjusted to the level of student understanding. The use of media tools such as images, videos, and audio further enhance instruction clarity. Adequate facilities and consistent teacher supervision was carried out for successful implementation. Evaluation through attendance records and moral assessments indicates improved student participation and discipline. Challenges, such as students' lack of awareness and disciplinary issues, are addressed through educational approaches and character-building programs. Overall, PAI teachers' communication skills significantly impact the habituation of congregational prayer, positively influencing students' character and discipline development. The study underscores the importance of effective communication in religious education to nurture essential spiritual practices among young students.